Health Education and Practice of Warm Water Compress Therapy in Reducing Dysmenorrhea Pain among Female Students at Nusantara Private Senior High School, Lubuk Pakam (JURNAL PENGMAS KESTRA (JPK), 2025)
Adolescent girls are in a developmental phase marked by the maturation of the reproductive system, one of which is indicated by the onset of menstruation. However, menstruation is often accompanied by dysmenorrhea, which may cause discomfort, reduce learning concentration, and interfere with school activities. Dysmenorrhea remains a prevalent reproductive health problem, including in North Sumatra Province. One safe, simple, and easily applicable non-pharmacological method to alleviate menstrual pain is the use of warm compresses, although adolescents’ knowledge and skills in applying this method correctly are still limited. This Community Service Program aimed to improve knowledge and skills and to reduce the intensity of dysmenorrhea through health education and hands-on practice of warm compress application. The activity was conducted at SMA Swasta Nusantara Lubuk Pakam and involved 10 female students experiencing dysmenorrhea, selected using purposive sampling. The program stages included a pretest, reproductive health education, demonstration, hands-on practice of warm compress application, and posttest evaluation. Instruments used comprised a participant characteristics questionnaire, a Numeric Rating Scale (NRS) for pain assessment, a knowledge questionnaire, and an observation checklist for skills evaluation. The results showed that the mean pain score decreased from 5.6 (moderate pain) to 2.2 (mild pain), indicating a reduction of 3.4 points. The proportion of participants with good knowledge increased from 30% to 80%, and all participants demonstrated improved understanding. In terms of skills, 80% of participants achieved a very good category and 20% a good category. These findings indicate that education combined with hands-on practice is an effective and feasible approach for managing dysmenorrhea among adolescent girls.